Adalimumab in Japanese patients with active ulcers of pyoderma gangrenosum: Final analysis of a 52‐week phase 3 open‐label study. Issue 5 (3rd March 2022) - Yamasaki, Kenshi; Yamanaka, Keiichi; Zhao, Yiwei; Iwano, Shunsuke; Takei, Keiko; Suzuki, Koji; Yamamoto, Toshiyuki
Abstract: In this 52‐week, phase 3 open‐label study, efficacy and safety of adalimumab were evaluated in Japanese patients with active ulcers due to pyoderma gangrenosum (PG) during a 26‐week treatment period and another 26‐week extension period. Patients received adalimumab 160 mg at week 0, 80 mg at week 2, and 40 mg every week from week 4. At week 26, 12 of 22 patients (54.5%, p  < 0.001) achieved the primary efficacy endpoint of PG area reduction 100 (PGAR 100, complete skin re‐epithelialization) for the target ulcer. Nine patients with Physician's Global Assessment (PGA) score of 1, 2, or 3, including four patients achieving PGAR 100, continued into the extension period. During the extension period, six of nine patients (66.7%) achieved PGAR 100 for the target PG ulcer at 52 weeks; one patient who achieved PGAR 100 before week 26 experienced a relapse 162 days after achieving this endpoint. Six patients achieved PGA 0 by week 52, and one patient reported new ulcers at day 57 of the extension period. Continued improvements from study baseline to week 52 were observed in pain (mean [95% CI] –4.0 [−6.5 to −1.5] numeric rating scale) and Dermatology Life Quality Index (−7.3 [−15.1 to 0.4]). In addition to the adverse events (AE) reported in 18 patients (including four serious AE) through week 26 (most commonly infections [ n  = 11]), there was one 1 additional AE (infection) during the extension period. These results suggest that adalimumab is effective and generally well tolerated in Japanese patients with active PG ulcers.